Ocorrência de opacidade de cápsula posterior em cães pós-facoemulsificação, com ou sem a utilização de lente intraocular dobrável e efeitos do Nd: Yag Laser - Conceição, Luciano Fernandes da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Cataracts are among the most common eye diseases in dogs, being the phacoemulsification method the one that best suits in their therapy. The posterior capsule opacification (PCOs) are among the most common complications and manifest themselves in weeks or months after cataract surgery. Intraocular lenses (IOLs) used in the correction of postoperative hyperopia, are mentioned as useful in the prevention of PCOs , especially the foldable acrylic ones with truncated or square edges. However, when PCOs are set up, capsulotomies are required as a treatment. In human patients, the effects of the Nd:YAG laser are recognized as a noninvasive and secure technique against such problems. To compare the results of eyes of dogs that received foldable acrylic intraocular lenses with eyes of aphakic dogs, after phacoemulsification, during a period of 180 days it was used 20 dogs of several breeds, male or female , ranging from 3 to 7 years old , with juvenile, immature or mature (n = 10 immature, mature n = 10) bilateral cataracts . Two groups (G1 = with implantation of intraocular lens and G2 = no artificial lens implant) were randomly formed and all dogs had both eyes operated. After the surgery, the patients were weekly evaluated for the presence or absence of synechiae, discoria, intraocular pressure, uveal inflammation and presence or absence of posterior capsule opacification during a period of 180 days. At 60, 90, 120, 150 and 180 days after surgery, the posterior capsule images were captured for evaluation of their opacity. Eyes with score 2 or 3 of opacity were underwent to capsulotomy by Nd:YAG laser. Ordinal categorical variables were compared (G1 X G2) using the chi-square and Fisher´s exact test. Quantitative variables were compared using ANOVA with Tukey post test. Synechiae were observed in the same frequency in both groups .G2 showed 30 % more discoria when compared to G1 Intraocular pressure did not differ between the groups. The ...

A catarata elenca-se entre as afecções oculares mais freqüentes em cães, sendo a facoemulsificação o método que melhor se adequa à sua terapia. As opacidades de cápsula posterior (OCPs) estão entre as complicações mais comuns e se manifestam em semanas ou meses após a facectomia. Lentes intraoculares (LIOs), empregadas na correção da hipermetropia pós-cirúrgica, são citadas como úteis na prevenção das OCPs, especialmente as acrílicas dobráveis, com bordas truncadas ou quadradas. Entretanto, quando OCPs se estabelecem requerem-se capsulotomias como forma de tratamento. Em pacientes humanos, reconhecem-se os efeitos do Nd:YAG laser como técnica não invasiva e segura frente a tais intercorrências. Para se compararem resultados de olhos de cães que receberam lentes intraoculares acrílicas dobráveis com olhos de cães afácicos, após facoemulsificação, durante um período de 180 dias, utilizaram-se 20 cães de raças diversas, machos ou fêmeas, que variaram de 3 a 7 anos de idade, apresentando catarata juvenil , imatura ou madura (imatura n = 10 , madura n = 10) bilateral. Dois grupos (G1 = com implante de lente intraocular e G2 = sem implante de lente artificial) foram formados aleatoriamente e todos os cães tiveram ambos os olhos operados. Após a cirurgia, os pacientes foram avaliados, semanalmente, quanto a presença ou a ausência de sinéquias, discoria, pressão intraocular, inflamação uveal e presença ou não de opacidade de cápsula posterior durante um período de 180 dias. Aos 60, 90, 120, 150 e 180 dias após a cirurgia, imagens da cápsula posterior foram capturados para avaliação da sua opacidade. Olhos com score 2 ou 3 de opacidade foram submetidos à terapia de capsulotomia pelo Nd:YAG laser. Variáveis categóricas ordinais foram comparadas (G1 X G2) empregando-se o teste de qui-quadrado e o teste exato de Fisher. Variáveis quantitativas foram comparadas empregando-se ANOVA com pós teste de Tukey
Keywords: Cão; Olhos; Faco-emulsificação; Lentes intra-oculares; Nd-YAG lasers; Phacoemulsification